Quantitative easing by the fed and international capital flows - Sameer Khatiwada (Graduate Institute of International and Development Studies, 2017)
By employing a novel dataset on international capital flows, this paper examines the impact of Fed's quantitative easing (QE) policies on flows to emerging markets economies (EMEs) and the EU countries. Episodes of QE are examined separately, with the last episode divided between pre- and post-tapering. We find evidence that QE was associated with an increase in capital inflow, while tapering was associated with a period of retrenchment. The magnitude of the impact varied by different episodes of QE and the types of assets (bonds or equities). Our results show that the EU countries behaved differently than the EMEs. We also find support for the importance of "pull factors" and individual country characteristics for capital inflows. However, the paper shows that episodes of QE accounted for most of the variation in capital inflows during 2008-2014. G20 statements during the episodes of QE show that countries are increasingly cognizant of their inability to control flows and have thus called for better monetary policy coordination to avoid excessive volatility and negative spillovers.
Keywords: E44; E52; E58; F32; F41; F42; 330; quantitative easing (QE); spillovers; capital flows; emerging market economies (EMEs)